1988
DOI: 10.1007/bf00558251
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue concentrations of ceftazidime in burn patients

Abstract: The pharmacokinetics and tissue concentrations of ceftazidime have been investigated in 8 patients with severe burns (20-80% of body surface area) undergoing skin transplantation 2 to 21 days after injury. Two prophylactic doses of ceftazidime were administered as 1 g i.v. bolus injections with an 8 h interval. Blood, urine, burn blister fluid and tissue were frequently sampled and drug concentrations were analyzed by HPLC. The kinetics of ceftazidime was the same after each dose. In these patients the pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
23
4

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 17 publications
5
23
4
Order By: Relevance
“…Loss of antibiotics through the wound has been shown for other agents [23]. Despite the negative relationship between C max and burn severity demonstrated in our study, which might suggested transwound clearance, we have not found any relationship between Cl AMK and the area and degree of the burn.…”
Section: Discussioncontrasting
confidence: 83%
“…Loss of antibiotics through the wound has been shown for other agents [23]. Despite the negative relationship between C max and burn severity demonstrated in our study, which might suggested transwound clearance, we have not found any relationship between Cl AMK and the area and degree of the burn.…”
Section: Discussioncontrasting
confidence: 83%
“…The authors concluded that imipenem pharmacokinetics in burn patients were similar to those in normal volunteers. Ceftazidime pharmacokinetics in burn patients have also been reported (24). The authors found that, compared with those of other patients, the apparent volume of distribution, CLNR, and CLT were higher, while tl/23, CLR, and urinary recovery of ceftazidime were lower in burn patients.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, there is a dearth of reported information regarding P-lactam antibiotics. Only reports on ceftazidime (24) and imipenem (3) are available.…”
mentioning
confidence: 99%
“…These changes often require increased doses to maintain adequate concentrations for successful treatment of severe infections (3,4,12,13,29,34,35). The potential for suboptimal dosing of antibiotics is particularly of concern in this population because of the frequency of infection with difficult, less-susceptible pathogens along with highly variable pharmacokinetics.…”
mentioning
confidence: 99%